Global and Local Reactivity Indexes Applied to Understand the Chemistry of Graphene Oxide and Doped Graphene - Cortes-Arriagada, D (2013)
At the density functional theory level, the electronic reactivity of oxidized and doped (with N, B, and P) graphene (G) has been analyzed. Molecular hardness and electrophilicity were used as global reactivity descriptors, while those at the local level, Fukui functions, Mulliken charges and molecular electrostatic potential were used in the order to characterize the intramolecular and intermolecular reactivity. These descriptors show that in GO, the global and local reactivity of the basal plane is improved mainly by hydroxyl groups, which improve besides the physisorption of small molecules, while, the active carbon atoms around the functional group would allow enhancement of the consecutively chemisorption. Furthermore, epoxide, carbonyl and carboxyl groups allow mainly enhancement of intermolecular non-covalent interactions. On the other hand, doping with N and B atoms increases the electrophilic character and the reactivity in the bulk. Specifically, in N-doped G, N and around carbon atoms would be able to serve as active sites of detection by frontier-controlled processes, explaining the improvement in electrochemical sensing; in addition, electron-deficient carbon atoms around N enhance the physisorption. Respecting the B-doped G, dopant and carbon atoms adjacent to B act as donor sites, suggesting that adsorption of cations on B-doped G is a frontier-controlled process; moreover, positively-charged B atoms enhance charge-controlled interactions with polarized molecules, and consecutively, in a frontier-controlled step, chemisorption is possible. Finally, P-doping increases the electrophilic reactivity in the bulk; also, P atoms enhance the physisorption of chemical species with negatively-charged centers or lone-pair electrons, and consecutively, chemisorption on P is possible. © 2012 Springer-Verlag Berlin Heidelberg.